Preliminary Concept of Alternative Agrarian Reform for Justice: The Social Tenure Domain Model (STDM) Approach to Constructing a Just Society in Indonesia - Lina Jamilah; Arif Firmansyah (Unissula, 2023)
The implementation of agricultural reform comprises the enactment of access and asset reform. In order to ensure compliance with the aforementioned instructions, the Indonesian government issued Presidential Regulation Number 86 of 2018, which stipulates the commencement of agricultural reform as a means to support asset and access reform. The primary goal of access arrangements is to enhance access to finance and various forms of support to enhance welfare outcomes through land utilization. This particular methodology is frequently denoted as community empowerment. The normative juridical research technique, commonly known as library law research, perceives law as a normative system that possesses autonomy, independence, and distinctiveness from society. The methodology necessitates the utilization of a conceptual framework that incorporates a social tenure domain model and a legal perspective. The research findings indicate that the central concept of agrarian reform for justice entails implementing a comprehensive land administration system encompassing diverse land claims and rights through the utilization of the Social Tenure Domain Model (STDM) approach. The concept of the social method pertains to a theoretical framework that centers on the impact of social influences on human behavior. The notion of the STDM explores the interconnection between individuals and land.